Mazari UAV Adaptive Autopilot System Design and Implementation - Adiansyah, Sonny (2013)
A Master of Science thesis in Mechatronics Engineering by Sonny Adiansyah entitled, "Mazari UAV Adaptive Autopilot System Design and Implementation," submitted in June 2013. Thesis advisor is Dr. Mohammad Amin Al Jarrah. Available are both soft and hard copies of the thesis.